Critical Analysis of Islamic Family Law Reform: Corpus and Classification - Anggraeni, Luciana; Sayyaf, R. Tanzil Fawaiq (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This article critically analyzes Islamic family law reforms with a focus on the legal corpus and its classification. The main aim of this research is to explore the reasons behind efforts to reform Islamic family law and to identify gaps that exist in the legal context. The core issues examined include the differences between traditional Islamic family law and current reform efforts, as well as the relevance and social implications of these changes in an increasingly modern society. The research methodology used includes analysis of legal documents, comparative studies between Islamic family law systems in various countries, and a review of the views of experts and relevant stakeholders. The findings of this research highlight the complexity in implementing Islamic family law reform, both in terms of theory and practice. The conclusion of this article emphasizes the importance of a holistic and inclusive approach in designing Islamic family law reform that can accommodate various views and social and legal needs in modern society.